(3GSJKeGQ ebGdI ajKGZhQS GdeYQhaI HGdPgHjI JaSjQ HQbdSs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3ajKGZhQS ef LRjQI SHGehS hjbGd Ef GdcgGfI CfPQJ HehdOg hGfg hdO ef YPQGA s
(3BNQgG (B:s
(3hgGgfG JfbWY KeQI ebGdI ajKGZhQS GdPgHjI HJaSjQ HQbdS hddg GdMeO hdGTcQ cESJMbGbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/8) s
Keywords: (3GdadSaI hGdefWbs